A praying life : connecting with God in a distracting world - Miller, Paul E., 1953- (NavPress, 2009)
Paul Miller shares his insights and conclusions about how to connect the broken pieces of your life and allow prayer -- even poorly delivered -- to fill the gaps with meaning and substance. --from publisher description